Insular networks for emotional processing and social cognition: comparison of two case reports with either cortical or subcortical involvement - Couto, Blas; Sedeño, Lucas; Sposato, Luciano A.; Sigman, Mariano; Riccio, Patricia M.; Salles, Alejo; Lopez, Vladimir; Schröder, Johannes; Manes, Facundo; Ibanez, Agustin (Cortex, 2013)
Introduction - The processing of the emotion of disgust is attributed to the insular cortex (IC), which is also responsible for social emotions and higher-cognitive functions. We distinguish the role of the IC from its connections in regard to these functions through the assessment of emotions and social cognition in a double case report. These subjects were very rare cases that included a focal IC lesion and a subcortical focal stroke affecting the connections of the IC with frontotemporal areas. - Materials & methods - Both patients and a sample of 10 matched controls underwent neuropsychological and affective screening questionnaires, a battery of multimodal basic emotion recognition tests, an emotional inference disambiguation task using social contextual clues, an empathy task and a theory of mind task. - Results - The insular lesion (IL) patient showed no impairments in emotion recognition and social emotions and presented with a pattern of delayed reaction times (RTs) in a subset of both groups of tasks. The subcortical lesion (SL) patient was impaired in multimodal aversive emotion recognition, including disgust, and exhibited delayed RTs and a heterogeneous pattern of impairments in subtasks of empathy and in the contextual inference of emotions. - Conclusions - Our results suggest that IC related networks, and not the IC itself, are related to negative emotional processing and social emotions. We discuss these results with respect to theoretical approaches of insular involvement in emotional and social processing and propose that IC connectivity with frontotemporal and subcortical regions might be relevant for contextual emotional processing and social cognition.